Unificación de las normas para impugnar en sede administrativa los actos administrativos de la administración pública, para evitar problemas de inseguridad jurídica en el País - Granda Granda, Miguel Alcívar (2012)
The Constitution of the Republic of Ecuador, in Article 173 states that "the administrative acts of any State authority may be challenged, both administratively and before the corresponding organs of the judiciary, in the same way in Art . 76 paragraph 7, letter m) of this body of law, stipulates that the right to the protection of people, including their ability to appeal a judgment or settlement in all proceedings in which they decide on their rights, that is determined to the challenge as a general constitutional right to search any person to rectify the act of a public body, considered as erroneous and prejudicial to their interests. The right to challenge in administrative acts of public authority is implemented mainly through institutions called administrative appeals process, but under Ecuadorian law, each state agency has different rules on what to do with the procedures challenge of its resolutions, which prevents a true application of the universal principles of law and the constitutional, unlike most advanced countries in administrative justice, such as Peru, Colombia and Spain, which have unified procedures to challenge entire public administration. With this background it is concluded in Ecuador has become indispensable, the unification of legal rules governing the procedures to challenge acts for all state functions.